Efficacy of Erythromycin in treatment of pityriasis rosea (A double-blind, placebo-controlled clinical trial) - Mohammad Dehghan; Naser Behnampour; Nazila Alborzi (مجله دانشگاه علوم پزشکی گرگان, 2008)
Background & Objective: Pityriasis rosea is an acute inflammatory dermatosis with an unknown cause. Although it is a self limitted disorder and has no chronic side effects (nevertheless it will take between 3-6 weeks) but it may continue for two months. In order to shorten pityriasis rosea course and remove itching and skin lesions, it is advisable to cure the disease with an appropriate drug. Based on the above, the present study was performed to investigate efficacy of Erythromycin in comparison with placebo and improve this disease period. Materials & Methods: A randomized double blind clinical trail was carried out on typical pityriasis rosea patients who had referred to 5th Azar clinic Gorgan-Iran during December 2004-May 2005. 46 patients were selected and randomly divided into two groups (23 patients in each one). Since it was a double blind study, treatment for two weeks was prescribed then the cure rate was measured during second, fourth and sixth week. In case group, Erythromycin 1gr/day was prescribed and continued for two weeks. In the other group only placebo was prescribed. Statistical analysis: Pearson chi-square analysis with 2- sided p value was applied to compare the distribution of pityriasis rosea between patients by using Sspss-11.5 software Regard to the kind of study and qualitative attribute, we used comparison between ratios in order to analyze them. Meaningful level for these tests was α=0.05. Results: Even though we gained good results in case group during second, fourth and sixth week after treatment, but there was no significant difference between these two groups at α=0.05. Conclusion: This investigation shows that Erythromycin has little effect on pityriasis rosea period. Therefore we suggest complementary study with larger samples in future.